Securitization and Asset Prices - Yunus Aksoy; Henrique S. Basso (Center for Economic Studies and ifo Institute (CESifo), 2015)
During the 15 years prior to the global financial crisis the volume of securitized assets transacted in the US grew substantially, reflecting a change in the nature of the financial intermediation process. Together with increased securitization of assets, financial entities, who participate more heavily in the asset-backed security (ABS) market and hold a diversified portfolio of assets, have also become more relevant. As a result, the volume of securitization, although traditionally associated with credit markets, influences the outcomes of other asset markets. We investigate the link between securitization and asset prices and show that increases in the growth rate of the volume of ABS issuance lead to a decline in both the bond and equity premia. We then build a model of bank portfolio choice where the creation of synthetic securities may occur. The pooling and tranching of credit assets relaxes both the funding and the risk constraints financial entities face allowing them to increase balance sheet holdings. This increase in asset demand depresses the compensation for undertaking risk in the economy, confirming our empirical results. Crucially, we show that declines in the compensation for risk taking in equity and bonds due to securitization may not be related to a decline in actual risk.
Keywords: E44; G12; G20; 330; pooling and tranching; equity; government bonds; bank portfolio; risk premia